The Significance of Katsuwonus Pelamis (Skipjack Tuna) Organoleptic in the Relation with the Kid’s Nutritional Status - Susanti, Neny Yuli (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The food processing of fish is varied, and one of the ways is to cook it as fish meatball soup. This research aims to test the organoleptic of fish meatball soup, as the processed food of skipjack tuna. The organoleptic-tested fish processed food was given to underweight kids (under red mark), which then the increase of their nutritional status would be observed. The population as well as the sample of this research is mothers who own underweight under-five-year-old children in Banyuputih Public Health Center area, Situbondo region. This research used t-paired test or mann whitney to process the analyzing result before and after the research.